Facile, efficient and eco-friendly synthesis of 5-sulfenyl tetrazole derivatives of indoles and pyrroles - Kuhn, Bruna L. (2014)
A concise, two-step eco-friendly approach towards the synthesis of 5-sulfenyl tetrazole derivatives of indoles and pyrroles, is reported. The synthesis comprises the oxone-mediated thiocyanation of the starting heterocycles towards intermediate 3-thiocyanato indoles and 2-thiocyanato pyrroles, and their subsequent treatment with sodium azide in 2-propanol/water under zinc bromide promotion.